2021
DOI: 10.3390/atmos12081038
|View full text |Cite
|
Sign up to set email alerts
|

Towards Possible Laminar Channels through Turbulent Atmospheres in a Multifractal Paradigm

Abstract: In this paper, developments are made towards simulating complex atmospheric behavior using turbulent energy cascade staging models developed through scale relativity theories. Such theoretical considerations imply gauges that describe atmospheric parameters as multifractal functions undertaking scale symmetry breaking at each stage of the turbulent energy cascade. It is found that gauges of higher complexity (in this case, a Riccati-type gauge) can exhibit more complex behavior accordingly, such as both dilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In fact, this model is produced by presupposing , , and . Recently, however, we have expanded upon this model in previous studies and successfully implemented it in a practical framework through lidar data [ 11 , 13 ]. It has been found that this model belongs to a class of gauges obtained from scale transition laws in the context of multifractality and that a similarly simple, yet slightly different, model containing a scale resolution parameter can give improved results [ 13 ].…”
Section: On Turbulent Scale Evolution Through Gauges and Equivalences With The Logistic Mapmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, this model is produced by presupposing , , and . Recently, however, we have expanded upon this model in previous studies and successfully implemented it in a practical framework through lidar data [ 11 , 13 ]. It has been found that this model belongs to a class of gauges obtained from scale transition laws in the context of multifractality and that a similarly simple, yet slightly different, model containing a scale resolution parameter can give improved results [ 13 ].…”
Section: On Turbulent Scale Evolution Through Gauges and Equivalences With The Logistic Mapmentioning
confidence: 99%
“…Recently, however, we have expanded upon this model in previous studies and successfully implemented it in a practical framework through lidar data [ 11 , 13 ]. It has been found that this model belongs to a class of gauges obtained from scale transition laws in the context of multifractality and that a similarly simple, yet slightly different, model containing a scale resolution parameter can give improved results [ 13 ]. By maintaining a constant , but by adding the scale resolution parameter, the following equation: leads to multiple vortices that have their own differing fractal dimensions, i.e., leads to multifractal flow [ 13 ].…”
Section: On Turbulent Scale Evolution Through Gauges and Equivalences With The Logistic Mapmentioning
confidence: 99%
See 3 more Smart Citations